Jorge Martínez Barrera, La política en Aristóteles y Tomás de Aquino. (Pamplona: Cuadernos de Anuario Filosófico, 2001), 202 páginas. - Massini Correas, Carlos I. (2001)
Fil: Massini Correas, Carlos I. Universidad de Mendoza; Argentina